2021
DOI: 10.3390/ijerph18137093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Physiological Response during Cardiopulmonary Resuscitation with Personal Protective Equipment: A Randomized Crossover Study

Abstract: The use of personal protective equipment (PPE) is required for the self-protection of healthcare workers during cardiopulmonary resuscitation (CPR) in patients at risk of aerosol transmission of infectious agents. The aim of this study was to analyze the impact of personal protective equipment on physiological parameters during CPR. A randomized, quasi-experimental, crossover design was used. The study was carried out in a training and simulation emergency box and the total sample consisted of 20 healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The final sample consisted of sixteen (16) RNs. Previous studies [ 11 , 12 , 17 , 18 ] have also included a similar number as the study sample. The RNs performed the scenario two times—once with PPE-Conv and another time with PPE-PAPR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample consisted of sixteen (16) RNs. Previous studies [ 11 , 12 , 17 , 18 ] have also included a similar number as the study sample. The RNs performed the scenario two times—once with PPE-Conv and another time with PPE-PAPR.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies have assessed the impact of the use of PPE on professionals but in settings that are far different from the clinical environment, using very low-fidelity activities, without the main objective of measuring the impact of one’s own use of PPE [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This time was intended for physiological adjustment to environmental conditions and to allow cortisol and lactate concentrations to adjust to a resting state. 10 During this timeframe, the participants remained seated in a chair. The study took place from 8:30AM to 11:30AM (time of relatively higher levels of cortisol).…”
Section: Experimental Procedures and Materialsmentioning
confidence: 99%
“…2 However, these studies have been performed in single-rescuer situations, without the possibility of rest periods, and resuscitations of short durations (two-to-four minutes). 8,10 The effect of PPE on resuscitation is not consistent. While some studies have found significant changes in CPR quality, 11,12 a recent systematic review and meta-analysis showed that the rate and depth of chest compressions are not inferior when wearing PPE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation